Prehospital management and outcomes of patients calling with chest pain as the main complaint - Sughra Ahmed; Filip Gnesin; Helle Collatz Christensen; Stig Nikolaj Blomberg; Fredrik Folke; Kristian Kragholm; Henrik Bøggild; Freddy Lippert; Christian Torp-Pedersen; Amalie Lykkemark Møller (International Journal of Emergency Medicine)
Abstract Background Chest pain is a frequent cause of health care contacts. We examined the prehospital management, in-hospital discharge diagnoses, and mortality of patients calling a non-emergency and emergency medical service with chest pain. Methods The Copenhagen Emergency Medical Services (EMS) consists of a non-emergency medical helpline (calls to 1813) and emergency medical service (1-1-2 calls). We included all calls to the Copenhagen EMS with a primary complaint of chest pain from 2014 to 2018 in Copenhagen, Denmark. The outcomes were: emergency response (ambulance dispatch, other transports/self-transport/home visits, self-care, and unknown/cancelled response), in-hospital diagnosis within 7 days after the call (cardiovascular, pulmonary, or other non-cardiovascular/pulmonary) and 30-day mortality. Results Among 4,834,071 calls, 91,671 were registered with chest pain at the Copenhagen EMS. The first call for each patient was kept for analysis (n = 66,762). In total, 91.4% were referred to the hospital, 75.8% (n = 50,627) received an ambulance and 15.6% (n = 10,383) received other transport/self-transport/home visits. Overall, 26.9% (n = 17,937) were diagnosed with a cardiovascular disease, 5.2% (n = 3,490) a pulmonary disease, 52.8% (n = 35.242) other non-cardiovascular/pulmonary disease, and 15.1% (n = 10,093) received no diagnosis. Among ambulance-transported patients, the prevalence of cardiovascular discharge diagnoses was higher (32.1%) and fewer received no diagnosis (11.0%). Cardiovascular disease was less prevalent among patients not transported by ambulance and patients not referred to hospital at all (2-13.4%) and in patients ≤ 40 years of age (< 10%). The 30-day mortality was below 5% regardless of diagnosis (0.6-4%), and 65,704 (98.4%) were still alive 30 days later. Conclusion Nearly all patients calling with chest pain were referred for treatment. Among ambulance-transported patients, around half of the patients did not have a cardiovascular/pulmonary disease. While current practices appear reasonable, improved differentiation of chest pain patients in telephone consultations could potentially both improve the treatment and management of these patients and reduce the in-hospital burden of non-acute chest pain consultations.